2005
DOI: 10.1111/j.1365-2885.2005.00682.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple dose pharmacokinetics and acute safety of piroxicam and cimetidine in the cat

Abstract: The purpose of this study was to evaluate the multiple dose pharmacokinetics and acute safety of piroxicam and cimetidine alone and in combination in cats. Seven healthy cats were included in this randomized-crossover study. The cats were assigned to groups designated to receive cimetidine alone (15 mg/kg, p.o., q12 h), piroxicam alone (0.3 mg/kg, p.o., q24 h), and piroxicam combined with cimetidine (both at aforementioned doses). The cats were dosed for 10 days followed by at least a 2-week washout period bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…12 However, none of the cats in our study received that drug combination. 22 The drug is generally well tolerated in dogs but can cause clinically relevant gastric ulceration; renal and hepatic toxicoses may also develop. Single-agent treatment with piroxicam has been used in many dogs with TCC of the urinary bladder; reported median survival associated with that regimen is 181 days.…”
Section: Discussionmentioning
confidence: 99%
“…12 However, none of the cats in our study received that drug combination. 22 The drug is generally well tolerated in dogs but can cause clinically relevant gastric ulceration; renal and hepatic toxicoses may also develop. Single-agent treatment with piroxicam has been used in many dogs with TCC of the urinary bladder; reported median survival associated with that regimen is 181 days.…”
Section: Discussionmentioning
confidence: 99%
“…2003). Multiple‐dose pharmacokinetics and acute safety have been evaluated for piroxicam administered at 0.3 mg kg −1 daily for 10 days, with and without concurrent cimetidine administration (Heeb et al. 2005).…”
Section: Specific Drugsmentioning
confidence: 99%
“…The mean half‐life increased from 11 hours on day 1 to 14 hours on day 10. Cimetidine reduced the half‐life of piroxicam, but not significantly (Heeb et al. 2005).…”
Section: Specific Drugsmentioning
confidence: 99%
See 1 more Smart Citation
“…Single and multi-dose pharmacokinetics of piroxicam has been established in the cat. Heeb et al 10,12 found that 0.3 mg/kg appeared well tolerated as a single oral or intravenous dose, and also when dosed orally for 10 consecutive days. There is very little published information on the clinical use of piroxicam in cats and the effective dose is unknown.…”
mentioning
confidence: 99%